Human organotypic brain slice cultures: a detailed and improved protocol for preparation and long-term maintenance - Bak, Aniella; Koch, Henner; van Loo, Karen M.J.; Schmied, Katharina; Gittel, Birgit; Weber, Yvonne; Ort, Jonas; Schwarz, Niklas; Tauber, Simone C.; Wuttke, Thomas V.; Delev, Daniel (Journal of Neuroscience Methods, 2024)
The investigation of the human brain at cellular and microcircuit level remains challenging due to the fragile viability of neuronal tissue, inter- and intra-variability of the samples and limited availability of human brain material. Especially brain slices have proven to be an excellent source to investigate brain physiology and disease at cellular and small network level, overcoming the temporal limits of acute slices. Here we provide a revised, detailed protocol of the production and in-depth knowledge on long-term culturing of such human organotypic brain slice cultures for research purposes. We highlight the critical pitfalls of the culturing process of the human brain tissue and present exemplary results on viral expression, single-cell Patch-Clamp recordings, as well as multi-electrode array recordings as readouts for culture viability, enabling the use of organotypic brain slice cultures of these valuable tissue samples for basic neuroscience and disease modeling (Fig. 1).
CRIS-Team Scopus Importer:2024-03-08
Keywords: Human brain; Human cerebrospinal fluid; In vitro models; Multi-electrode array; Neuronal network; Organotypic brain slice cultures; Single-cell patch-clamp recordings; Viral transduction